Losing her father in final semester, Siti Hawa resolves to achieve excellence at UMPSA - Mohammad Syafiq Syahmi, Suhaimi (UMPSA, 2024)
GAMBANG, 29 October 2024 – Siti Hawa’s determination to make her family proud, especially in honour of her late father, was proven today as she successfully earned a Bachelor of Chemical Engineering degree (Part-Time Programme) during the 19th Convocation Ceremony of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).